Obesity and adiposity promote the development of non-suppurative otitis media: a Mendelian randomization study - Yan, Xin; Chen, Suhua (Frontiers in Medicine, 2024)
Background: Observational studies have found that obesity is associated with the development of nonsuppurative otitis media(NSOM), but the causality and pathogenesis are unclear. The aim of our study was to investigate the association between obesity, lipid metabolism, and NSOM at the genetic level. METHODS: We performed a bidirectional two-sample Mendelian randomization (MR) study to examine the causal relationship between obesity, lipid metabolism-related factors ,and NSOM by using the datasets obtained from the IEU Open GWAS project. Furthermore, multivariate MR(MVMR) on lipid indicators was conducted to validate the results. We then used obesity or body mass index(BMI) as the exposure and NSOM as the outcome to search for possible mediators in lipids and adipokines. RESULTS: Using NSOM as the outcome, we found 9 positive exposure results related to obesity and lipid metabolism. Among them, obesity, BMI, body fat percentage, waist circumference, hip circumference, and resistin were risk factors while apolipoprotein A1(apoA1), high-density lipoprotein cholesterol(HDL-C), and nerve growth factor(NGF) were protective factors. Then we used obesity and lipid metabolism-related factors as outcomes and NSOM as the exposure to perform MR analysis, which failed to obtain positive results. In the MVMR analysis, we found that HDL cholesterol and apoA1 remained causally associated with NSOM after correction for other potential confounders. Coincidentally, When obesity or BMI was used as the exposure, NSOM as the outcome, HDL cholesterol or apoA1 can serve as mediators for them through two-step MR analysis. In the MR analysis for mediation, obesity, and BMI reduced the production of HDL or apoA1, which can serve as protective factors affecting the development of NSOM. CONCLUSION: At the genetic level, obesity and adiposity may promote the development of NSOM, while NSOM has no effect on obesity and adiposity. Obesity can also encourage the progress of NSOM by reducing HDL cholesterol /apoA1. Resistin may be a potential risk factor for NSOM, whereas NGF may be a potential protective factor.